Gambaran Waktu Tunggu Pelayanan Resep pada Pasien BPJS Rawat Jalan Di Instalasi Farmasi Rumah Sakit X Mojokerto Periode Maret- April 2023 - Dewy Resty Basuki; Esti Ambar W (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Diabetes is one of a number of diseases that result in too much sugar levels in the blood (high blood glucose), treatment with the example of the drug Glibenclamide can reduce blood sugar levels gradually, so alternative treatment is needed from natural ingredients. One of the natural ingredients that contain chemical compounds Flavonoids, Coumarins, and Triterpenoids, which have activity lowering blood sugar levels. The purpose of this study was to determine the activity of melinjo peel extract against antidiabetes in mice to determine the most effective dose of lowering blood sugar levels in male mice, in this study using this research method using melinjo peel extract (Gnetum gnemon L) with a dose of 200mg/kgBB ,250mg/kgBW and a dose of 42mg/kgBW which aims to determine the effect of melinjo peel extract as a decrease in blood sugar levels in male mice, shows that melinjo peel extract (Gnetum gnemon L.) is the most effective in reducing sugar levels at a dose of 42mg/kgBW, compared with positive control and doses of 28mg/kgBW and 35mg/kgBW. The results of the study concluded that melinjo peel extract (Gnetum gnemon L) in the 28mg/kgBW, 35mg/kgBW and 42mg/kgBW dose groups were the most effective in reducing blood sugar levels. 42 mg/kg body weight. The conclusion is that there is antidiabetic activity in the extra skin of melinjo (Gnetum gnemon L.) both at doses of 28mg/kgBW, 35mg/kgBW and 42mg/kgBW but the most effective for reducing blood sugar levels is at a dose of 42mg/kgBW compared to the positive control. This data is supported by repeated ANOVA test with a significant value of p=0.012 (p>0.05), which means that all groups have significant differences in both the extract and the comparison group used.